Ceftazidime and cefotaxime--the clinician's choice. - Puthucheary, S.D.; Goldsworthy, P.J. (1989)
A review of two third-generation cephalosporins, ceftazidime and cefotaxime, is presented. Ceftazidime, often used as a single agent, has shown greater activity than cefotaxime against Pseudomonas aeruginosa and other Pseudomonas species, Enterobacteriaceae, Acinetobacter sp, and Enterobacter sp. It has been effective as monotherapy in the treatment of peritonitis, gynecologic infections, chronic bronchitis, and infections in patients with leukemia and granulocytopenia, as has cefotaxime when in combination with an aminoglycoside. Cefotaxime has shown good activity against most aerobic gram-negative bacilli and against Staphylococcus. It has been used in respiratory infections, urinary tract infections, and septicemia. In contrast to first-generation and most second-generation cephalosporins, third-generation cephalosporins have proven useful in some types of meningitis. Ceftazidime and cefotaxime successfully penetrate into the cerebrospinal fluid and cures of bacterial meningitis have been reported with both drugs. Both ceftazidime and cefotaxime have been successfully used in children, infants, and neonates, as well as adults. Safety profiles of ceftazidime compare favorably with those of other third-generation cephalosporins.